The role of glycogen synthase kinase-3 (GSK-3) protein in the development of myocardial hypertrophy in a rat model of diet induced obesity and insulin resistance - Lubelwana Hafver, Tandekile (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2012.